16
$\begingroup$

Let $\alpha$, $\beta$, $\gamma$, $\delta$ be the roots of $$z^4-2z^3+z^2+z-7=0$$ then find value of $$(\alpha^2+1)(\beta^2+1)(\gamma^2+1)(\delta^2+1)$$ Are Vieta's formulas appropriate?

$\endgroup$
43
$\begingroup$

There is no need to use Vieta's formulas. Let $$f(z)=z^4-2z^3+z^2+z-7=(z-\alpha)(z-\beta)(z-\gamma)(z-\delta).$$ Then, since $(i-a)(-i-a)=-i^2+a^2=1+a^2$, it follows that $$(\alpha^2+1)(\beta ^2+1)(\gamma^2+1)(\delta^2+1)=f(i)f(-i)=|f(i)|^2=|-7+3i|^2=49+9=58.$$

$\endgroup$
  • 1
    $\begingroup$ I loved your answer as it used the concept of complex numbers in a very easy way. $\endgroup$ – Rohan Shinde Oct 9 '17 at 2:19
8
$\begingroup$

Rearrange the equation to $z(2z^2-1)=z^4+z^2-7$ square this & substitute $y=z^2+1$ \begin{eqnarray*} (y-1)(2y-3)^2=((y-1)^2+(y-1)-7)^2 \\ y^4+\cdots +58 =0. \end{eqnarray*} Note that the roots of this polynomial will be $\alpha^2+1,\beta^2+1,\gamma^2+1,\delta^2+1$ and we have not calculated all the terms explicitly (only the ones required to obtain the product of these roots.) So $(\alpha^2+1)(\beta^2+1)(\gamma^2+1)(\delta^2+1)=\color{blue}{58}$.

$\endgroup$
  • 3
    $\begingroup$ [+1] One should say to the OP that forming the equation with transformed roots is a standard method for this kind of problems (substitution/elimination method), here done with the less calculation possible! $\endgroup$ – Jean Marie Oct 8 '17 at 16:58
3
$\begingroup$

transform the equation so that you get the desired roots.

so the given equation has roosts $\alpha, \ \beta,\ \gamma, \ \delta $ first transform $x \to \sqrt{x}$ so the new equation ha roots $\alpha^2, \ \beta^2,\ \gamma^2, \ \delta^2 $ then transform $x \to x-1$ to get the equation whose roots are $\alpha^2+1, \ \beta^2+1,\ \gamma^2+1, \ \delta^2+1 $

now the answer is product of roots of new equation.

$\endgroup$
3
$\begingroup$

You can do it by the Viete's theorem!

We obtain: $$\sum_{cyc}\alpha=2;$$ $$\frac{1}{4}\sum_{sym}\alpha\beta=1;$$ $$\sum_{cyc}\alpha\beta\gamma=-1$$ and $$\alpha\beta\gamma\delta=-7.$$ Thus, $$\prod_{cyc}(1+\alpha^2)=1+\alpha^2\beta^2\gamma^2\delta^2+\sum_{cyc}\alpha^2\beta^2\gamma^2+\frac{1}{4}\sum_{sym}\alpha^2\beta^2+\sum_{cyc}\alpha^2=$$ $$=1+49+\left(\sum_{cyc}\alpha\beta\gamma\right)^2-2\alpha\beta\gamma\delta\cdot\frac{1}{4}\sum_{sym}\alpha\beta+\left(\frac{1}{4}\sum_{sym}\alpha\beta\right)^2-2\sum_{cyc}\alpha\sum_{cyc}\alpha\beta\gamma+2\alpha\beta\gamma\delta+$$ $$+\left(\sum_{cyc}\alpha\right)^2-2\cdot\frac{1}{4}\sum_{sym}\alpha\beta=$$ $$=50+1-2\cdot(-7)\cdot1+1^2-2\cdot2\cdot(-1)+2\cdot(-7)+2^2-2=58.$$ Also we can use the following. $$(a^2+b^2)(x^2+y^2)=(ax+by)^2+(ay-bx)^2=(ax-by)^2+(ay+bx)^2.$$ Indeed, $$\prod_{cyc}(\alpha^2+1^2)=((\alpha+\beta)^2+(\alpha\beta-1)^2)((\gamma+\delta)^2+(\gamma\delta-1)^2)=$$ $$=((\alpha+\beta)(\gamma+\delta)-(\alpha\beta-1)(\gamma\delta-1))^2+((\alpha+\beta)(\gamma\delta-1)+(\alpha\beta-1)(\delta+\gamma))^2=$$ $$=\left(\frac{1}{4}\sum_{sym}\alpha\beta-\alpha\beta\gamma\delta-1\right)^2+\left(\sum_{cyc}\alpha\beta\gamma-\sum_{cyc}\alpha\right)^2=(1+7-1)^2+(-1-2)^2=58.$$ Done!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.